Investigations on physical characteristics of three-dimensional coil structure for MEMS magnetometer - Sulaiman, Nadzril; Yeop Majlis, Burhanuddin (Academy of Sciences Malaysia, 2013)
Measurement of low magnetic field has played an important role in many electronics applications such as navigation, military, non-destructive test, traffic detection as well as medical diagnosis and treatment. The presence of magnetic field, particularly its strength and direction, can be measured using magnetometer. There are many types of magnetometers being investigated through the years and one of the prominent types is fluxgate magnetometer. The main components of fluxgate magnetometer consisting of driving coils, sensing coils and magnetic core are developed by MEMS silicon processing technology. In this paper, an investigation on physical characteristics of the three-dimensional coil structure for a micro-scaled fluxgate magnetometer is presented. The physical characteristics such as width of the coil, distance between successive coils, and gap between the top and bottom coils which would influence the magnetic energy in magnetometer is discussed. In this work, finite-element method simulations to investigate the physical characteristics of the sensing coils were carried out, where the parameter of interest is the coils’ inductance as well as the magnetic flux density. Based on the simulation results, the varying of physical characteristics of the coils had its effects particularly in coil inductance, magnetic flux density, and magnetic energy. It could also be seen that the simulated results agreed with the theoretical aspects of magnetism in a coil. From the investigations, suitable coil dimensions were proposed.